MOTIF-MOTIF PADA TOKOH UTAMA DALAM NOVEL LOADED KARYA CHRISTOS TSIOLKAS - Muhammad Arief Budiman (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2011)
Australia is both a continent and a country. As a big nation, there are many cultural mix happenned in daily life come from various immigrants with their cultural background. This creates many problems caused by different culture of each citizen. Three problem points discussed in this research are: what is the main character's motive living without a job, what is the main character's motive rejecting to continue his education in higher level, and what is the main character's motive experiencing freesex and drugs. the approach used in this research is psychology of literature by applying Freud's Psychoanalysis Theory as a base to analyze personality structure, motive of actions, ego defense mechanism, and the effects from all habits done by the main character. The result of this research on novel Loaded shows that the main character as Australian teenager experiencing difficulty in finding his identity. Every action he took has motive to please himself. For avoiding any miseries, the main character done many kinds of ego defense mechanism. The effect of his actions to reach maximum happiness brings him into the life style which destroys himself.